Dual Alleviation of Acute and Neuropathic Pain by Fused Opioid Agonist-Neurokinin 1 Antagonist Peptidomimetics - Betti, Cecilia (ACS Med Chem Lett, 2015)
[Image: see text] Herein, the synthesis and biological evaluation of dual opioid agonists–neurokinin 1 receptor (NK1R) antagonists is described. In these multitarget ligands, the two pharmacophores do not overlap, and this allowed maintaining high NK1R affinity and antagonist potency in compounds 12 and 13. Although the fusion of the two ligands resulted in slightly diminished opioid agonism at the μ- and δ-opioid receptors (MOR and DOR, respectively), as compared to the opioid parent peptide, balanced MOR/DOR activities were obtained. Compared to morphine, compounds 12 and 13 produced more potent antinociceptive effects in both acute (tail-flick) and neuropathic pain models (von Frey and cold plate). Similarly to morphine, analgesic tolerance developed after repetitive administration of these compounds. To our delight, compound 12 did not produce cross-tolerance with morphine and high antihyperalgesic and antiallodynic effects could be reinstated after chronic administration of each of the two compounds.